Проекты Нового краеведения в неофициальной истории города: опыт Санкт-Петербурга - Troitskaya, Anna (Studia Rossica Posnaniensia, 2024)
The problem of interpreting local history is relevant to St. Petersburg, as to many other major historical cities. This article examines phenomena united by the concepts of local (spatial) myth and urban narrative, which go beyond official discourse. Alternative images of the city, based on its concealed places of interest contrast with one of the most widespread representations of St. Petersburg – its association with the heritage of imperial culture. The selection of memorable places and stories shifts from recognizable city landmarks to other objects that reveal the history and image of particular St. Petersburg sites, people’s daily lives and peripheral issues of urban life. This approach to the exploration of urban space, a phenomenon called New Local History, is presented and explained in the article as the rediscovery of the historical potential of the city. The examples given in the article also show the possible role of New Local History in encouraging residents to develop an interest in their own history, in the problems of modernity and in participating in socially significant projects. Trends in interaction with urban space and memory practices that offer alternative interpretations of the past have been identified in various socio-cultural initiatives. In the context of Russian memory politics, this approach often becomes oppositional.